The Role of Commanders’ Managerial Styles in Predicting Soldiers’ Deliberate Physical Self-Injury: The Mediating Role of Alexithymia - Azizi, Mohammad; Shadbafi, Mohammad (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to examine the role of commanders’ managerial styles in predicting soldiers’ deliberate physical self-injury, with alexithymia as a mediating variable. Methods and Materials: This study employed a descriptive correlational design using path analysis. The statistical population consisted of soldiers of the Islamic Republic of Iran Army in the northwest region of the country in 2024. A total of 198 soldiers were selected through multistage cluster random sampling. Data were collected using the Self-Harm Inventory (SHI), the Management Systems Questionnaire (LSQ), and the Toronto Alexithymia Scale (TAS). Descriptive statistics and Pearson correlation coefficients were computed, and the hypothesized model was tested using structural equation modeling with SPSS version 25 and AMOS version 24. Assumptions of normality, multicollinearity, and independence of errors were examined prior to model testing. Indirect effects were assessed using bootstrapping procedures. Findings: Results indicated that exploitative–authoritative management had a positive and significant direct effect on alexithymia (β = 0.37, p < .01) and deliberate physical self-injury (β = 0.29, p < .01). Benevolent–authoritative management showed significant negative direct effects on alexithymia (β = −0.27, p < .01) and deliberate physical self-injury (β = −0.19, p < .05). Alexithymia had a positive and significant direct effect on deliberate physical self-injury (β = 0.18, p < .05). Bootstrapping results demonstrated that alexithymia significantly mediated the relationships between exploitative–authoritative management (β = 0.07, p < .05) and benevolent–authoritative management (β = −0.05, p < .05) with deliberate physical self-injury. Consultative and participative management styles did not show significant direct or indirect effects. The model explained 25% of the variance in deliberate physical self-injury. Conclusion: The findings suggest that commanders’ managerial styles play a significant role in shaping soldiers’ vulnerability to deliberate physical self-injury, both directly and indirectly through alexithymia. Authoritarian leadership may increase risk by intensifying emotional processing deficits, whereas benevolent leadership appears to exert a protective effect.